Socio-spatial inequality of privatisation approach to service delivery of electricity in Nigeria - Olamide Eniola, Victor; Abd. Aziz, Norsiah; Jaffar, Abdul Razak (2015)

(untitled)
The pursuit of the public welfare should be of paramount concern to any good government to alleviate poverty in tandem with the Millennium Development Goals. As developing nations in the world aspire to meet the vision 20:2020, it is imperative that whatever economic approach, model or strategy adopted must not be at the expense of the welfare of the citizens. In western industrialised world, privatisation is used to improve the lives of citizens where market competition in the provisions of goods and services thrive for the benefit of an egalitarian and equitable society. However, the outcomes of privatisation in most developing countries are not as intended, as the social costs far supersede its benefits, owing to some reasons the paper is out to discuss. As a conceptual paper with discussions based predominantly on secondary data sources cum literature, this paper seeks to explain the socio-inequality and poverty laden outcomes of privatisation policy of service delivery of electricity in Nigeria. Privatisation policy has been claimed to adversely impinged the welfare of the populace, making the poor, poorer. Based on identified theoretical gap of non-harmonising policies with actual situation on ground, this paper argues that the issues of social inequality are occasioned by privatisation policy, and identifies the shortcomings of this approach to service delivery of electricity. The paper recommends taking areal reality and spatial dimension into consideration for decision making, policy resolution and implementation in Nigeria.